ABCs of Windows 98 - Crawford, Sharon and Salkind, Neil J. (San Francisco Sybex, 1998)
Designed for users who are new to Windows X, this text provides information and guidance on how to begin to take advantage of shortcuts, mouse button tricks, long file names, customization options, Internet connectivity, and other Windows X Internet capabilties.
Keywords: Operating systems (Computers) -- Microsoft Windows (Computer file)